ANALISIS KEGIATAN PEMBELAJARAN BERBASIS PENDEKATAN SAINTIFIK DI KELAS V SEKOLAH DASAR - Suci Tri Indah Sari (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
At present, Indonesia uses the 2013 education curriculum or national curriculum in education. The most important thing in the 2013 curriculum is the use of a scientific approach. Teachers still have difficulty applying the scientific approach to teaching and learning activities. The use of descriptive research methods by researchers must describe the data obtained at the time of data collection. This includes a description of the learning plan and learning data in class Vb 91 of SD Negeri Pekanbaru. Data collection is done through observation, surveys and documentation studies using data analysis techniques in the form of data collection and subsequent data reduction to present data for inference. Class Vb teacher has planned learning activities according to the scientific approach. Learning planning activities carried out by making lesson plans that are made by studying the syllabus, textbooks and textbooks by explaining the steps of a scientific approach in accordance with textbook information. The teacher has done learning in a scientific approach, doing 5M activities, namely observing, asking questions, collecting data, debating and communicating. However, the hardest part is asking questions that can still be answered by giving advice to students.